Overview of research studies on underground coal gasification in Slovenia - Berčič, Gorazd (JET on-line, 2014)
The first concepts regarding the commercial processing of lignite date back to 1948, and in 1961 the EKK power plant was formally established. It was liquidated in 1968, due to low oil and gas prices on the world market. In 1962, the first Slovenian research project analysing underground coal gasification (UCG) technologies was published. In 1980, the activities that should be taken to perform the first Slovenian UCG test in 1984 were specified. From 1983 to 1987, the first laboratory experiments were conducted.The purpose of the experiments was to study the impact of operating parameters on coal combustion and gas quality. Since 2000, interest in UCG technology has been rising again. Research has been funded by the CMV and implemented by ERICo, IREET, FNT, NIC and CMV. The main purpose of these studies was to obtain information on the state of the art in the world regarding UCG technologies and the geological characterization of coal seams appropriate for UCG. From 2010 to 2012, the CMV produced a study on the efficiency of a power plant using gas produced by lignite UCG. In 2011, the RCE started a project under which the first Slovenian gasification test is planned to be carried out in-situ in 2014.
Keywords: coal gasification; energetika; lignite; pregled; premog; research overview; Slovenia; Slovenija; UCG; underground; uplinjanje premoga